Concentrated fish oil (Lovaza®) extends lifespan and attenuates kidney disease in lupus-prone short-lived (NZBxNZW)F1 mice. (June 2013) - Halade, Ganesh V; Williams, Paul J; Veigas, Jyothi M; Barnes, Jeffrey L; Fernandes, Gabriel
A growing number of reports indicate that anti-inflammatory actions of fish oil (FO) are beneficial against systemic lupus erythematosus (SLE). However, the majority of pre-clinical studies were performed using 5–20% FO, which is higher than the clinically relevant dose for lupus patients. The present study was performed in order to determine the effective low dose of FDA-approved concentrated FO (Lovaza®) compared to the commonly used FO-18/12 (18-Eicosapentaenoic acid [EPA]/12-Docosahexaenoic acid [DHA]). We examined the dose-dependent response of Lovaza® (1% and 4%) on an SLE mouse strain (NZBxNZW)F1 and compared the same with 1% and 4% placebo, as well as 4% FO-18/12, maintaining standard chow as the control. Results show for the first time that 1% Lovaza® extends maximal lifespan (517 d) and 4% Lovaza® significantly extends both the median (502 d) and maximal (600 d) life span of (NZBxNZW)F1 mice. In contrast, FO-18/12 extends only median lifespan (410 d) compared to standard chow diet (301 d). Additionally, 4% Lovaza® significantly decreased anti-dsDNA antibodies, reduced glomerulonephritis and attenuated lipopolysaccharide-induced pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) in splenocytes compared to placebo. 4% Lovaza® was also shown to reduce the expression of inflammatory cytokines, including IL-1β, IL-6 and TNF-α, while increasing renal anti-oxidant enzymes in comparison to placebo. Notably, NFκB activation and p65 nuclear translocation were lowered by 4% Lovaza® compared to placebo. These data indicate that 1% Lovaza® is beneficial, but 4% Lovaza® is more effective in suppressing glomerulonephritis and extending life span of SLE-prone short-lived mice, possibly via reducing inflammation signaling and modulating oxidative stress.